2003
DOI: 10.1021/ol035535m
|View full text |Cite
|
Sign up to set email alerts
|

Water Exclusion Reaction in Aqueous Media:  Nitrone Formation and Cycloaddition in a Single Pot

Abstract: [reaction: see text] The formation of nitrone (a water exclusion reaction) in aqueous media using surfactant and subsequent cycloaddition in the same pot, a new example of green chemistry, is reported. The control of regioselectivity favors the formation of trans-5-substituted isoxazolidine. This work not only may lead to an environmentally benign system but also will provide a new aspect of reactions in water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…Although no clear evidence showed that micelles could significantly accelerate organic reactions (Diels-Alder cycloaddition, 14 epoxidation 15 ), use of micellar catalysis has been recently reported for a 1,3-dipolar reaction with nitrones. 16 Due to the polar dipolarophile character, interactions with the organized medium could be responsible for this acceleration. We chose to test the four surfactants SDS, DTAC, CTAB, and OGH ( Figure 2) for their anionic, cationic, and neutral properties.…”
Section: Resultsmentioning
confidence: 99%
“…Although no clear evidence showed that micelles could significantly accelerate organic reactions (Diels-Alder cycloaddition, 14 epoxidation 15 ), use of micellar catalysis has been recently reported for a 1,3-dipolar reaction with nitrones. 16 Due to the polar dipolarophile character, interactions with the organized medium could be responsible for this acceleration. We chose to test the four surfactants SDS, DTAC, CTAB, and OGH ( Figure 2) for their anionic, cationic, and neutral properties.…”
Section: Resultsmentioning
confidence: 99%
“…Commercially unavailable allylic bromides or mesylates were prepared according to reported methods. [917] It is worth mentioning that decarbonylation [18] was observed in some cases during conversion of the acetal to the aldehyde. This side reaction could be suppressed to some extent by using more dilute HCl.…”
Section: Resultsmentioning
confidence: 99%
“…The chemistry and utilities of surfactants is well investigated. [11] Because of their hydrophobic and hydrophilic nature, the surfactants form micelles with water-insoluble organic compounds and promote the desired reactions to occur in water (e.g., the water extrusion reactions in the formation of nitrones [12] and esters [13] in water may be mentioned). In continuation of our research interests in hydrated media, [14] we now first report here the cleavage of imines to give carbonyls (aldehydes and ketones) and acetanilides with moisture-sensitive Ac 2 O mediated by a surfactant (SDS) in water at room temperature with excellent yields (Scheme 1).…”
Section: Sds/ac 2 O/h 2 O: Surfactant-mediated Cleavage Of Imines Witmentioning
confidence: 99%